An enhanced role and expanded developmental origins for gamma‐aminobutyric acidergic interneurons in the human cerebral cortex. Issue 4 (20th May 2014) - Clowry, Gavin J.
Abstract Human beings have considerably expanded cognitive abilities compared with all other species and they also have a relatively larger cerebral cortex compared with their body size. But is a bigger brain the only reason for higher cognition or have other features evolved in parallel? Humans have more and different types of GABAergic interneurons, found in different places, than our model species. Studies are beginning to show differences in function. Is this expanded repertoire of functional types matched by an evolution of their developmental origins? Recent studies support the idea that generation of interneurons in the ventral telencephalon may be more complicated in primates, which have evolved a large and complex outer subventricular zone in the ganglionic eminences. In addition, proportionally more interneurons appear to be produced in the caudal ganglionic eminence, the majority of which populate the superficial layers of the cortex. Whether or not the cortical proliferative zones are a source of interneurogenesis, and to what extent and of what significance, is a contentious issue. As there is growing evidence that conditions such as autism, schizophrenia and congenital epilepsy may have developmental origins in the failure of interneuron production and migration, it is important we understand fully the similarities and differences between human development and our animal models.